2009
DOI: 10.4314/mcd.v3i1.44132
|View full text |Cite
|
Sign up to set email alerts
|

Bats as bushmeat in Madagascar

Abstract: Bats are eaten by people throughout Madagascar and although the larger species like Pteropus rufus, Eidolon dupreanum, Rousettus madagascariensis and Hipposideros commersoni are preferred, small insectivorous bats are also eaten. The national hunting season for bats is widely ignored and both unsuitable hunting practices and high offtake represent a serious threat to bat populations in some areas. Bat bushmeat may be an important source of protein for Malagasy people during periods of food shortage but in gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 36 publications
2
71
0
1
Order By: Relevance
“…12.1), as well as in Cameroon, Congo Republic, Democratic Republic of Congo (DRC), Equatorial Guinea and Gabon. High levels of hunting have also been reported in the past from islands off Africa-the Comoros, Madagascar, Mauritius and Rodrigues and São Tomé and Príncipe as well as Pemba Island, Tanzania (Jenkins and Racey 2008;Carvalho et al 2014), although conservation efforts have reduced this pressure in some of these islands (Trewhella et al 2005).…”
Section: Africamentioning
confidence: 99%
See 3 more Smart Citations
“…12.1), as well as in Cameroon, Congo Republic, Democratic Republic of Congo (DRC), Equatorial Guinea and Gabon. High levels of hunting have also been reported in the past from islands off Africa-the Comoros, Madagascar, Mauritius and Rodrigues and São Tomé and Príncipe as well as Pemba Island, Tanzania (Jenkins and Racey 2008;Carvalho et al 2014), although conservation efforts have reduced this pressure in some of these islands (Trewhella et al 2005).…”
Section: Africamentioning
confidence: 99%
“…In some places, hunting laws are hard to understand and therefore not followed by hunters. In Madagascar for example, bats can be hunted legally between May and August or February to May, depending on the species (Jenkins and Racey 2008). In addition, according to the regulations, hunting is allowed only during the day, and game species cannot be hunted at their roost.…”
Section: Regulated Huntingmentioning
confidence: 99%
See 2 more Smart Citations
“…Brooke & Tschapka (2002) documented the unsustainable hunting of P. tonganus on Niue Island in the South Pacific, stemming from the belief of islanders that taboo areas on the island, which they did not enter, harboured an inexhaustible supply of bats, >1500 of which were shot when the population was estimated at between 2000 and 4000 ind. Jenkins & Racey (2008) reported that although the endemic Pteropus rufus, Eidolon dupreanum, Rousettus madagascariensis and Hipposideros commersoni were the most commonly eaten bats in Madagascar, a wide range of small insectivorous bats also are taken, and the high harvesting represents a serious threat to local populations. The killing of the molossid Cheiromeles torquatus for food in Borneo is also causing serious concern , and the unsustainable exploitation of insectivorous bats for food in Laos has been described by Francis et al (1999), with thousands of Tadarida being harvested during exit from a cave and then subsequently smoked for sale.…”
Section: Huntingmentioning
confidence: 99%